2015
DOI: 10.3390/ijerph120403417
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Free-Living Amoebae from Different Water Sources in Italy

Abstract: Free-living amoebae (FLA) are protozoa ubiquitous in Nature, isolated from a variety of environments worldwide. In addition to their natural distribution, some species have been found to be pathogenic to humans. In the present study a survey was conducted in order to evaluate the presence and to characterize at molecular level the isolates of amoebic organisms collected from different water sources in Italy. A total of 160 water samples were analyzed by culture and microscopic examination. FLA were found in 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 30 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…Vermamoeba vermiformis is one of the most common FLA to have been isolated from different water systems (Rhoads et al 2015;Montalbano Di Filippo et al 2015;Lu et al 2015;Armand et al 2016). It is also frequently recovered from hospital water networks as shown by several authors (Rohr et al 1998;Thomas et al 2006;Ovrutsky et al 2013;Pagnier et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Vermamoeba vermiformis is one of the most common FLA to have been isolated from different water systems (Rhoads et al 2015;Montalbano Di Filippo et al 2015;Lu et al 2015;Armand et al 2016). It is also frequently recovered from hospital water networks as shown by several authors (Rohr et al 1998;Thomas et al 2006;Ovrutsky et al 2013;Pagnier et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Di Filippo et al study confirmed that culture method is not precise enough to detect of free-living Amoebae [ 8 ]. In the study, a total of 160 water samples was analyzed for FLA by PCR method.…”
Section: Discussionmentioning
confidence: 99%
“…Acanthamoeba has been divided into different genotypes (T1-T20) based on rRNA gene [ 8 ]. Among Acanthamoeba genotypes, the most prevalent type is T4 that cause disease in human [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, even the use of automated extraction, PCR and DNA sequencing requires time-consuming procedures consisting in the preliminary steps of isolation of the species of interest [ 4 ]. The paper by Montalbano et al [ 34 ] describes a study to evaluate the presence of free-living amoebae (FLA). Identification of FLA species/genotypes, based on the 18S rDNA regions, allowed to identify 18 (39.1%) Acanthamoeba isolates (genotypes T4 and T15) and 21 (45.6%) Vermamoeba vermiformis isolates.…”
Section: Rapid and Efficient Methods To Monitor The Presence Of Emmentioning
confidence: 99%